2019
DOI: 10.4257/oeco.2019.2303.27
|View full text |Cite
|
Sign up to set email alerts
|

FIRST RECORD OF THE PARASITE BAT FLY Basilia mimoni THEODOR & PETERSON, 1964 (DIPTERA: NYCTERIBIIDAE) IN COLOMBIA

Abstract: The ectoparasites of bats belonging to the family Nycteribiidae (Insecta, Diptera) are highly specialized and little is known about this family in the New World. Only two genera of the family Nycteribiidae are catalogued in Colombia, Basilia, with seven species, and Hershkovitzia, with only one species. This is the first report of Basilia mimoni in Colombia. Two females and one male were collected from the bat Gardnerycteris keenani (Chiroptera, Phyllostomidae). These records broaden the distribution range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Therefore, according to the host distribution, the B. tiptoni records from Graciolli et al (2007) probably comes from G. keenani for Colombia, Costa Rica, and Panama, and from G. crenulatum for Venezuela and Brazil. Thus, this species would have also a second degree of specificity like it was proposed for B. ferrisi (i.e., Pastrana-Montiel et al, 2019), because it keeps associated with two bat species in a solely genus (Gardnerycteris). This is a high specificity degree and each fly species distribution is associated with the distribution of their hosts (G. keenani and G. crenulatum).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Therefore, according to the host distribution, the B. tiptoni records from Graciolli et al (2007) probably comes from G. keenani for Colombia, Costa Rica, and Panama, and from G. crenulatum for Venezuela and Brazil. Thus, this species would have also a second degree of specificity like it was proposed for B. ferrisi (i.e., Pastrana-Montiel et al, 2019), because it keeps associated with two bat species in a solely genus (Gardnerycteris). This is a high specificity degree and each fly species distribution is associated with the distribution of their hosts (G. keenani and G. crenulatum).…”
Section: Resultsmentioning
confidence: 87%
“…Finally, an occurrence map for Basilia species was constructed in ArcMap, including the herein presented records, the museum specimens (some type localities) listed in the Catalogue of Diptera of Colombia (Graciolli et al, 2016) and the recently recorded species B. ferrisi (Pastrana-Montiel et al, 2019). For most of those records the original listed localities were georreferenced and completed or corrected, this was necessary as some of the specific localities lack full details (e.g., municipalities) or were assigned to another department not consigned in the original labels, but the specific localities allowed us to find and solve those inconsistences (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 125 Streblidae species reported in Colombia and Venezuela (81 and 107 respectively; Wenzel 1976 ; Tarquino-Carbonell et al 2015 ; Dick et al 2016 ; Duran et al 2017; Calonge-Camargo and Pérez-Torres 2018 ; Guerrero 2019 ; Liévano-Romero et al 2019 ; Ascuntar-Osnas et al 2020 ; Raigosa Álvarez et al 2020 ; López Rivera et al 2022 ), 124 have been documented for the Orinoquia in ~ 96 bat species of the families Emballonuridae , Molossidae , Mormoopidae , Natalidae , Noctilionidae , Phyllostomidae , and Vespertilionidae ( Wenzel 1976 ; Dick et al 2016 ; Guerrero 2019 ; Liévano-Romero et al 2019 ; López Rivera et al 2022 ). Similarly, of the 16 Nycteribiidae reported in Colombia and Venezuela (11 and 13, respectively; Wenzel and Tipton 1966 ; Graciolli et al 2016 ; Pastrana-Montiel et al 2019 ; Raigosa Álvarez et al 2020 ; López Rivera et al 2022 ), 12 have been found in the Orinoquia (two in Colombia, 12 in Venezuela; Wenzel and Tipton 1966 ; Graciolli et al 2016 ; López Rivera et al 2022 ). Besides the high number of bats and bat flies documented in the Orinoquia, the interaction structure that might be evaluated using ecological or interaction networks ( Dormann et al 2009 ), has not been addressed.…”
Section: Introductionmentioning
confidence: 80%
“…It is noteworthy that the families Streblidae and Nycteribiidae have been the primary focus of research in the Neotropical region. As evidenced by various publications, 68 species have been documented in Peru (Minaya et al, 2021), 82 in Colombia (Dick et al, 2016;Pastrana-Montiel et al, 2019), 130 in Venezuela (Guerrero, 2019;Guimarães, 1972;Wenzel, 1976), and 119 in Brazil Hrycyna et al, 2019).…”
Section: Introductionmentioning
confidence: 96%